Polycentric governance model for transformative adaptation in Morocco: Institutional mapping - Ait El Mekki, Abdelkader; Amarasinghe, Upali; Saleth, Rathinasamy Maria; Amarnath, Giriraj; Brouziyne, Youssef (CGIAR Climate Resilience Initiative, 2022)
This paper mapped the institutions involved in planning, funding, implementing, maintaining and monitoring, and evaluating of the adaptation interventions in Morocco. It considered the following interventions implemented through the Green Morocco Plan for mapping institutions. 1). Adoption of Water Saving Program in irrigation 2). Adoption of resilient cropping patterns, and 3). Improvement of the investment climate in agriculture. The mapped institutions include institutional actors such as ministries, departments, local authorities, public establishments, professional organizations, funding agencies, etc., and non-institutional actors such as unorganized farmers, private operators, and households.